Analysis of software and hardware configuration management for pre-production vehicles - A case study at Volvo Car Corporation - Bordyk, Volha (My University, 2012)
Modern vehicles are no longer just mechanical; most of the car’s functionality is controlled by software, embedded into electronic control units (ECUs). The functionality of a vehicle is driven by customer expectations and leads to product variety since customers want their own personalized and unique car. ECU configurations consisting of different software and hardware play a vital role in providing the variability. In the automotive industry there is a tendency for shorter development cycles and several parallel projects. This combined makes keeping track of software and hardware configurations challenging, especially in pre-production vehicles where changes are introduced very often. There is also a risk that testing is performed on the wrong vehicle configuration. This can potentially lead to increasing costs and time losses. In this case study existing systems, tools and process work flows have been investigated and analysed at Volvo Car Corporation. An existing software and hardware configuration management system, used in the after market, was evaluated to what extent it could be reused. Based on the analysis, a software and hardware configuration prototype tool has been designed and implemented. The results have shown that it is possible to minimize the time necessary for preparing test setups (vehicle configurations), however limitations were found in both current processes and systems.
Keywords: Information Technology; Informationsteknik